Kajian Subtitusi Terigu Dengan Pasta Sukun (Arthocorpus altilis fosberg) Dan Pasta Labu Kuning (Cucurbita moschata durch) Pada Pembuatan Mi Basah - Hotman Manurung; Rosnawyta Simanjuntak (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The noodle circulating in the market and which we often consume the main ingredient is wheat flour so that the nutrient components such as fiber and carotenoids contained in noodle is very minimal. To increase the content of fiber and carotene noodle it is necessary to substitute flour with local food containing fiber and carotenoids. For example breadfruit and pumpkin. This study aims to determine how the influence of the amount of pumpkin paste and breadfruit as the substitution of flour to the characteristics of wet noodles and to the color preferences test and to determine the effect of storage duration on carotenoid content of wet noodles. The experiment was conducted by non factorial randomized design by comparing the amount of pumpkin paste to breadfruit paste and storage duration. The results showed that water content, ash content and protein content were not influenced by the ratio of the number of pumpkin paste to breadfruit paste. But the fiber content increased from 1.22% to 3.16% and carotenoid levels from 0.07 ppm to 0.10 ppm. The color preference level increases from 1.86 (dislikes) to 3.35 (like). Time storage can lower carotenoid levels from 0.105 ppm at 0 days storage to 0.08 ppm at 4 days. The conclusion of flour substitution with breadfruit paste and pumpkin paste can increase the fiber content and wet carotenoid noodles. Storage results in decreased carotenoid levels.